Medical students on the COVID-19 frontline: a qualitative investigation of experiences of relief, stress, and mental health - Klasen, Jennifer M.; Poljo, Adisa; Sortino, Rosita; Bogie, Bryce J. M.; Schoenbaechler, Zoe; Meienberg, Andrea; Nickel, Christian; Bingisser, Roland; LaDonna, Kori A. (Frontiers in Medicine, 2023)
Objective: During the early stages of the COVID-19 pandemic, medical students were abruptly removed from clinical rotations and transitioned to virtual learning. This study investigates the impact of this shift on students' well-being and preparedness for advanced training. Methods: Through qualitative research methods, including semi-structured interviews, the experiences of medical students working on the COVID-19 frontline were explored. Results: The comprehensive findings of the study shed light on the profound emotional journey that medical students embarked upon during the relentless public health crisis. Within the chaos and overwhelming demands of the pandemic, medical students discovered a profound sense of purpose and fulfillment in their contributions to the welfare of the community. Despite the personal sacrifices they had to make, such as long hours, limited social interactions, and potentially risking their own health, students reported feelings of relief and gratitude. Conclusion: Tailored support systems for medical students' well-being are crucial for improving healthcare delivery during crises. Medical schools should adopt a holistic curriculum approach, integrating interdisciplinary learning and prioritizing student well-being. Recognizing the pandemic's impact on students and implementing targeted support measures ensures resilience and contributes to an improved healthcare system.